Pelatihan Berbahasa Jawa Dalam Komunikasi di Media Sosial Bagi Remaja - Prima Veronika; Budi Waluyo; Tya Resta Fitriana (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service activity is to implement language politeness by using Javanese uploads according to the right situation and context on social media. The methods used include expository, discussion, modeling and observation. The results of the service show that there are still many teenagers today who are reluctant to use Javanese to communicate in the virtual world and the real world. Some teenagers also still feel shy when invited to communicate using Javanese. The service team tried to invite participants to do hands-on practice using the modeling method. Participants are invited to interact using good and correct Javanese according to the level of speech and the interlocutor. The communication carried out is conveying information, opinions, suggestions, criticisms that are often done in the virtual world and the real world.